Process for the preparation of polymeric absorbents - Lele, Ashish Kishor; Varghese, Shyni; Badiger, Manohar V.; Mashelkar, Raghunath Anant (2009)
The invention discloses a process for the preparation of polymeric absorbents useful for gelling organic liquids. The process comprises mixing one or more monomers with a cross-linking agent, a free radical initiator, an optional solvent, optionally in the presence of a transition metal source and subjecting the mixture so obtained to a conventional polymerisation method. The polymer is removed, crushed to obtain polymer powder, washed with solvent and dried by conventional methods to remove unreacted monomers, followed by swelling in alcohols to obtain the desired product.

Polyelectrolytes in dilute solution: viscometric access to coil dimensions and salt effects - Suresha, P. R.; Badiger, Manohar V.; Wolf, Bernhard A. (RSC Advances, 2015)
Copolymers of acrylamide (AM) and diallyldimethylammonium chloride (DADMAC), differing in molar masses M (52.3 to 227 kDa) and degrees of charging y (0.2 to 0.6), were studied with respect to their viscometric behavior in dilute aqueous solutions containing variable amounts of NaCl. Complementary measurements were performed on a Brookhaven 90 plus particle size analyzer. M dominates the intrinsic viscosities [eta]. For the viscometric interaction parameters B this is only true for large concentrations of extra salt. [eta] and B as a function of solvent salinity follow Boltzmann laws. Coil dimensions, determined either via dynamic light scattering or viscometry, agree well. For low salt contents of the solvent the radii decrease with rising polymer concentration, whereas they increase for high salt concentrations; at a characteristic salinity of the solvent they become independent. Zeta potentials grow from +20 to +40 mV as y goes up.

Porous poly(ethylene glycol)-polyurethane hydrogels as potential biomaterials - Divakaran, Anumon V.; Torris, Arun A. T.; Lele, Ashish K.; Badiger, Manohar V. (Polymer International, 2015)
We report the synthesis of porous poly(ethylene glycol)-polyurethane (PEG-PU) hydrogels using PEG-4000 as a soft segment and 4,4-methylenebis(cyclohexylisocyanate) as a hard segment. The degree of swelling in the hydrogels could be controlled by varying the amount of crosslinking agent, namely 1,2,6-hexanetriol. Structural characterization of the hydrogels was performed using solid-state C-13 NMR and Fourier transform infrared spectroscopy. Wide-angle X-ray diffraction studies revealed the existence of crystalline domains of PEG and small-angle X-ray scattering studies showed the presence of lamellar microstructures. For generating a porous structure in the hydrogels, cryogenic treatment with lyophilization was used. Scanning electron microscopy and three-dimensional micro-computed tomography imaging of the hydrogels indicated the presence of interconnected pores. The mechanical strength of the hydrogels and xerogels was measured using dynamic mechanical analysis. The observed dynamic storage moduli (E) for the equilibrium swollen and dry gels were found to be 0.15 and 4.2 MPa, respectively. Interestingly, the porous PEG-PU xerogel also showed E of 5.6 MPa indicating a similar mechanical strength upon incorporating porosity into the gel matrix. Finally, preliminary cytocompatibility studies showed the ability of cells to proliferate in the hydrogels. These gels show promise for applications as scaffolds and implants in tissue engineering. (c) 2014 Society of Chemical Industry
Keywords: hydrogels; permeability; poly(ethylene glycol); polyurethane; porosity

Product distribution in hydrogenation of styrene oxide over Pd/chitosan catalyst - Viswanadhan, Maya; Potdar, Aparna; Divakaran, Anumon V.; Badiger, Manohar V.; Rode, Chandrashekhar (Research on Chemical Intermediates, 2016)
Palladium-decorated chitosan catalyst was synthesized by an impregnation method by varying the Pd loading in the range of 1-6 %, and was evaluated for the regioselective hydrogenation of styrene oxide. In order to correlate the chemical and textural properties with the catalytic activity, all the prepared catalysts were characterized by techniques such as Fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy, transmission electron spectroscopy, thermo-gravimetric analysis, temperature-programmed desorption of NH3, and CO2 and N-2 physisorption. The synthesized catalysts were utilized for the efficient and regioselective ring opening of styrene oxide by hydrogenation under different conditions. The complete conversion of styrene oxide with 65 % selectivity for 2-phenyl ethanol and 33 % for 1-phenyl ethanol were obtained using 4 % Pd/CS catalyst at 70 degrees C temperature and 3 MPa pressure. The mechanism for the regio selective ring opening of styrene oxide to 1- and 2-phenyl ethanol was also proposed on the basis of properties of the catalyst support, catalytic activity and selectivity. These results indicated that the catalytic activity and selectivity of the catalysts were affected by the nature of support. Further, the basic properties of the support play an important role in the selectivity of the styrene oxide hydrogenation reaction.

Polysaccharide hydrogel incorporated carbon nanofiber microelectrode for designing neural interfaces - Torris, Arun; Badiger, Manohar V. (Journal of Bionic Engineering, 2019)
Bionic devices are an integral part of human life, and continuous innovations in their design and functions with the help of nanotechnology has revolutionized the area of neuroscience and technology. Bio-interfaces play a key role in bionic devices such as neural implants for efficient transfer of the signal to smart prosthetics. We report here on the design of a new microelectrode, comprising Carbon Nanofiber (CNF) and a biopolymer, namely carboxymethyl xyloglucan (CMX) hydrogel inside the CNF, which enhances the current density across the interface. Microelectrode was prepared by in-situ cross-linking of CMX inside CNF, with optimized CMX: CNF ratio, resulting in continuous ionic channels confined within the hollow core of CNF. Electron microscopy images of microelectrodes illustrate the formation of CMX hydrogel network inside the CNF hollow core without wrapping its surface. The presence of hydrogel in the CNF was confirmed by Scanning Electron Microscope (SEM) and Transmission Electron Microscopy (TEM). The electrochemical studies indicate the enhancement in charge density as well as the active surface area of the microelectrodes due to the presence of CMX hydrogel network. These microelectrodes have great potential as neural interfaces for designing smart prosthetics with voluntary control.